Role of Unified Power Flow Control in Voltage Power Transfer : A Critical Study - Rana, Pardeep; Singla, Dr. C.Ram (Innovative Research Thoughts, 2017)
The unified power flow controller (UNIFIED POWER FLOW CONTROL) is being used as a compensating and power control device in the power systems due to its easy build, high robustness and efficiency. Simulation results reveal that as far as voltage sag and swell are concerned both the two-level and five level inverter based UNIFIED POWER FLOW CONTROL exhibit the similar performance.As the five level inverter based UNIFIED POWER FLOW CONTROL generates nearly sinusoidal load voltage, its THD is observed to be 3.15%. It is 15.65% in the case of its two level counterparts. It may be noted that for power of good quality the THD must be less than or equal to 5% as per standards. Hence, with respect to power quality, the five level UNIFIED POWER FLOW CONTROL scheme has an edge over two level UNIFIED POWER FLOW CONTROL scheme.